HUBUNGAN KUALITAS PELAYANAN DENGAN KEPERCAYAAN MAHASISWA - Fatoni, Amin (JURNAL LENTERA BISNIS, 2019)
The Relationship between Service Quality with the Student's Trusty. The  objective of this research to know the lecturer’s and education service with competence, guarante of work fast and education service with student’s trusty in Polytechnic LP3I Jakarta Pasar Minggu campus. The research is carried out in campus Pasar Minggu due to the efficiency of time and place of respondent. The method of this research is by using descriptive statistic and hypothesis test. Base on the relation of service qualiy with students trusttuidance for the managerial, mainly in upgrading the service quality in term of upgrading the student's recommendation. The purpose of this research is to exa, it will result: lecturer’s competences have the significant relation eith student’s trusty. Promotion of guarantee of work fast has the significant relation with the students trusty, education service has the significant relation with the student’s trusty.Keyword : Studnts’s trusty, Lecturer’s Competence, Education Service